For India's Rural Poor, Growing Towns Matter More than Growing Cities - Gibson, John; Datt, Gaurav; Murgai, Rinku; Ravallion, Martin (World Bank, Washington, DC, 2017)
It is theoretically ambiguous whether growth of cities matters more to the rural poor than growth of towns. This paper empirically examines whether growth of India's secondary towns or big cities mattered more to recent rural poverty reduction, noting that data deficiencies have made this a difficult question to answer previously. Satellite observations of night lights are used to measure urban growth on the extensive and intensive margins in the context of a spatial Durbin fixed-effects model of poverty measures for rural India, calibrated to a panel of 59 regions observed four times over 1993-2012. The expansion of lit area had greater effect on the rural poverty measures than did intensive margin growth in the brightness of light from urban areas. For India's current stage of development, growth of secondary towns may do more to reduce rural poverty than big city growth, although the theoretical model suggests that cities may eventually take over from towns as the drivers of rural poverty reduction.